2011
DOI: 10.1128/jvi.05406-11
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 Virus-Like Particle Vaccine Elicits Cross-Reactive Neutralizing Antibodies That Preferentially Bind to the Oligomeric Form of Influenza Virus Hemagglutinin in Humans

Abstract: Transmission of pathogenic avian influenza viruses (AIV) from wild birds to domestic poultry and humans is continuing in multiple countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…2B). For calculation of the dissociation kinetics (off-rates), the SPR assay was performed with a low density of the antigen on the chip surface to provide only one epitope-paratope interaction for each intact antibody and was optimized using a MAb (bivalent IgG) and a Fab counterpart to obtain comparable kinetics (18,19,22,50). Similar results were obtained in SPR studies using mammalian rHA0.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…2B). For calculation of the dissociation kinetics (off-rates), the SPR assay was performed with a low density of the antigen on the chip surface to provide only one epitope-paratope interaction for each intact antibody and was optimized using a MAb (bivalent IgG) and a Fab counterpart to obtain comparable kinetics (18,19,22,50). Similar results were obtained in SPR studies using mammalian rHA0.…”
Section: Resultsmentioning
confidence: 84%
“…We showed previously that it is possible to generate a functional oligomeric rHA1 domain in the absence of the HA2 stalk domain (16,20,21,22). We further analyzed the impact of the oligomeric versus monomeric H5N1 HA1 proteins on immunogenicity and protective efficacy of the globular domain and evaluated the quality of antibodies generated in ferrets.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 A large trial of 2537 young adults receiving pandemic H1N1 vaccine showed that a 15 mg (HA) formulation stimulated seroprotective responses in 64-85% of seronegative subjects after one dose. 50 Dose-related trends for increased reactogenicity for formulations from 5 to 45 mg were reported.…”
Section: Recombinant Vlp-based Influenza Vaccinesmentioning
confidence: 99%
“…Neutralizing antibody titers were correlated with preferential binding to the oligomeric (vs. monomeric) form of recombinant HA1, which may present epitopes on virion spikes absent from monomeric forms. 49 That specificity is hypothesized to be important in providing cross-clade antibody responses. Anti-NA antibodies that were mapped to epitopes near the sialic acid binding site potentially could provide a functional benefit by inhibiting viral release.…”
Section: Recombinant Vlp-based Influenza Vaccinesmentioning
confidence: 99%
“…Influenza VLP vaccines have been suggested as promising alternative vaccine candidates (18,19) and have also been tested in clinical trials (20,21). Antibody responses to hemagglutinin (HA) after vaccination are the major immune correlates conferring protection against influenza virus infections.…”
mentioning
confidence: 99%